Postur Tubuh Pesenam Ritmik Ditinjau Dari Anthropometry Komposisi Panjang Tubuh Dan IMT (Universitas Negeri Semarang, 2021)
The purpose of the research to find out the posture profile of rhythmic gymnastics athletes at Wimilia Club and Gesaid Club is reviewed from anthropometry of body length composition and BMI. This research uses quantitative methods. Data analysis using percentage descriptive techniques. Data retrieval techniques use tests and measurements. The results of this study found that. The posture profile of rhythmic gymnastics athletes Klub Wimilia and Gesaid was reviewed from BMI with novice athletes malnourished by 13%, normal 73%, nutrition over 12%, and obesity 2%. Junior athletes with a nutritional BMI are less than 8%, normal 84%, and nutrition over 8%. Seniors with nutritional BMI are less than 20%, and normal 84%.Anthropometry of the body length composition of novice athletes shows that 44% is very in line with 23 athletes, 13% according to 7 athletes, 6% is quite in accordance with 3 athletes, 25% does not correspond to 13 athletes, and 12% is very incompatible with 6 athletes. Junior athlete body length composition 62% is very in accordance with 8 athletes, 15% does not correspond to 2 athletes, and 23% is very incompatible with 3 athletes. Senior athletes' body length composition of 40% is very in accordance with 2 athletes, 20% according to 1 athlete, and 40% does not correspond to 2 athletes. The conclusion of this study is that the average BMI normal category and body length composition is very appropriate. One of the factors supporting the performance and performance of rhythmic gymnastics athletes is the anthropometry of an athlete where the athlete's low body mass and ideal body length composition can support for rhythmic gymnastics athletes when performing movements.